A genre analysis of online crisis press releases on the MH370 flight incident / Nor Zulaikha Che Mat - Nor Zulaikha , Che Mat (2020)
A crisis press release is a piece of writing intended for the members of media and general public which specifically deals with a particular emergency case or incident. The use of press release in an event of crisis is crucial as a means of communication. This study aims to analyse the press releases on MH370 flight incident from a genre analysis perspective. 44 corporate press releases are collected from the Malaysia Airlines website and analysed. The findings of this study identify the communicative purposes of the crisis press release which are to disseminate information, to address issues and speculations as well as to assure and regain the reliability of the company. The mixing of informative and promotional genres is seen in the press releases through these communicative purposes as well as the rhetorical structure and strategies used to realise them. The findings and discussions may help the English for Academic Purposes teachers, researchers and novice writers in applied linguistics, crisis communication and public relation to write or further understand the online crisis press releases.